E-RESORCES UNTUK RISET DAN INOVASI - Rita Komalasari (Jurnal IPI (Ikatan Pustakawan Indonesia), 2019)
Moving Librarian must be active and creative to improve their skills and develop the creativities to serve and providing the best for their institution. Research and innovations that are increasingly intense, must be immediatly captures and responded by librarians as information and knowledge manager. The purpose of this paper is to provide tips to librarians, how to utilized e-resorces for research and innovation for lecturers and researchers. The methode used in this study is deskription methode base on application/implementation of the author’s experience to present information from various e-resources for lecturers and researchers. The information that presented to the lecturers and researchers proven can produce innovation that are beneficial for our country development.